Tadalafil Reversed H-89 – and Scopolamine – Induced Spatial Learning Impairments in Male Rats - Tabrizian, Kaveh; Amelinia, Fatemeh; Belaran, Maryam; Pourheidar, Soheil; Mirzaei, Hadi; Fanoudi, Sahar (Drug Research, 2021)
Accumulated evidence shows that the cAMP and cGMP signaling pathway plays an important role in memory function and neuronal plasticity. Phosphodiesterase 5 (PDE5) is a hopeful therapeutic target in AD (Alzheimer disease), and PDE5 inhibition may be a good therapeutic strategy for the treatment of AD. In the present study, the four-day bilateral intra-hippocampal infusion of H-89 as a protein kinase AII inhibitor (10 µM/side) and intra-peritoneal injections of tadalafil (20 mg/kg) and scopolamine (0.5 mg/kg) alone and also on combination on spatial learning in Morris water maze (MWM) were investigated. DMSO and saline were used as controls for H-89 and other mentioned drugs, respectively. Rats were trained for 4 days; each day included one block of four trials. Post- training probe trial tests were performed on day 5. Administration of H-89 and scopolamine led to a significant impairment in spatial learning compared to their related controls. But, combination of tadalafil/H-89 or tadalafil/scopolamine reversed H-89 or scopolamine- induced spatial learning deficits in MWM. Taken together, these results showed the probable regulatory effects of cGMP on cholinergic and cAMP/PKA signaling pathways in co-administrations of these mentioned drugs on spatial learning in MWM.
Keywords: cGMP/PKG; morris water maze; spatial learning; PKA II inhibitor; scopolamine